The constitutional and legal development of the Chinese presidency : the emperors' new clothes? - Zhang, Runhua, 1973- (Lexington Books, 2015)
Weaving together the study of both Chinese law and politics, this book investigates the evolution of the Chinese presidency and examines how presidential nomination, succession, and power have been determined by an ever-changing mixture of legal and political rules and traditions.